Satellite communication applied in a distributed application - Farstad, Werner; Johansen, Dag; Hartvigsen, Gunnar (Universitetet i Tromsø, 1994)
The paper describes the development of a prototype application for access to vital weather information from the Northern Atlantic sea region. The application gives meteorologists access to weather observations measured on sea vessels. Today the available information is very limited. On a daily basis, only 4-5 weather observations in the whole arctic sea-region are conducted. It is therefore suggested to use the available fishing-boat and the coast-guard as a basis for a full scale application. Communication is based on the Inmarsat-C global satellite system. This kind of communication offers limited data bandwidth, currently 600 bit/sec. In addition delays are introduced by the coast/earth-station due to message-queues and protocol-transformations. Based on the services of fered by the Inmarsat-C system, a simple prototype communication mechanism for data communication between terrestrial computers and computers on sea-vessels has been developed. It is, partly due to the nature of the satellite system, based on unreliable multicast of messages. A message may consist of a request which requires a reply (multicast RPC). Test results showed that doing a request and getting a reply takes from 1.5 - 4 minutes. The results depend on the type of message (supported by the Inmarsat-C system) which is used. The sea-vessels send weather observations in set intervals. This means higher availability on weather observations, and again a big step for meteorologists which today have to rely on observation which may be several hours old (if any at all).